Tumour characteristics of bilateral screen-detected cancers and bilateral interval cancers in women participating at biennial screening mammography. Issue 108 (November 2018) - van Bommel, Rob; Lameijer, Joost R.C.; Voogd, Adri C.; Nederend, Joost; Louwman, Marieke W.J.; Setz-Pels, Wikke; Strobbe, Luc J.; Tjan-Heijnen, Vivianne C.G.; Duijm, Lucien EM
Abstract: Background: Unilateral interval breast cancers show less favourable prognostic features than unilateral screen-detected cancers, but data on tumour characteristics of bilateral interval cancers in a systematically screened population are sparse. Therefore, we compared tumour characteristics of bilateral interval cancers with those of bilateral screen-detected cancers. Methods: We included all 468, 720 screening mammograms of women who underwent biennial screening mammography in the South of the Netherlands between January 2005 and January 2015. We collected breast imaging reports, biopsy results and surgical reports of all recalled women and of all women who presented with interval breast cancer. In women with synchronous bilateral breast cancer, the tumour with the highest tumour stage was defined as the index cancer. For comparison of data between both groups Fisher exact test and Chi-square test were used. Results: Synchronous bilateral cancer was diagnosed in 2.2% of screen-detected cancers (64/2947) and in 3.2% of interval cancers (24/753) (P = 0.1). Index tumours of bilateral screen-detected cancers and interval cancers showed similar characteristics, except for a larger proportion of T-stage 2 or worse (T2+) cancers among interval cancers (16/24 (66.7%) versus 23/58 (39.7%) (P = 0.03). Index cancers, compared to contralateral cancers, were less frequently stage T1 in both bilateral screen-detected cancers and bilateral interval cancers (35/64 (60.3%) versus 40/64 (88.9%) (P = 0.001) and 8/24 (33.3%) versus 18/24 (85.7%) (P < 0.001), respectively). In bilateral screen-detected cancers, contralateral cancers were more often stage 1a-c (P < 0.001) compared to index cancers. In bilateral index cancers, index cancers were more often of the lobular subtype (P < 0.001). Conclusion: Index cancers of bilateral screen-detected cancers and bilateral interval cancers show significant differences in tumour size, whereas nodal status, receptor status and final surgical treatment are comparable. In bilateral screen-detected cancer, index cancers had a significantly higher tumour stage. In bilateral screen-detected cancer, index cancers were more often the ductal invasive subtype compared to contralateral cancers.